Samuel Sebastian Wesley : a life - Horton, Peter (Oxford studies in British church music., 2004)
Irascible, truculent, but a brilliant musician. Any of these words could accurately describe Samuel Sebastian Wesley (1810-76), the foremost organist and church music composer of his generation. Peter Horton paints a detailed picture of the life and career of this remarkable man whose output includes such favourites as 'Blessed be the God and Father' and 'The wilderness'. - ;Born into one of England's best-known families, Samuel Sebastian Wesley (1810-76) was not only the foremost organist and church musician of his generation, but a vigorous campaigner for higher standards in cathedral music.